Loading

Loading

Substitute values of one equation into another.

(1) x+y+2z = -2; (2) 3x-y+14z=6; x+2y=-5 (3).

Substitute x in (1) and (2) from (3).

We get -y+2z=3 in (1).

We get -7y+14z=21 in (3).

Since (3) is (1)*7, we can conclude that the system has infinite solutions.

Solve the equation 8^(x-1) = 6^(3x) . Express your answer in terms of ln 2 and ln3 .

Answered by David G.

find the inverse function of the following: f(x) = 3x-5

Answered by Olivia T.

How does Euclid's algorithm give solutions to equations?

Answered by Abby R.

If f(x)=(x^3−2x)^5 , find f'(x).

Answered by Radovan S.